MicroRNA-21 expression as a novel diagnostic and prognostic biomarker in oral cancer: A narrative review - Llahfi, Yasminia Sambac Shofie Putri; Zafar, Anis Fatimah; ZV, Astrid Faradia; Pandora, Imelda Prisca; SD, Alfonsus Sindhu; NA, Muhammad Rafi; Widyanti, Salma Putri; Andrew, Emmanuel; Eliya A, Salsabilla; Alfisaida, Aliyya; Qadira R, Malika; Rodhiyah B, Aimmatur; Ramadhani, Puspita; Indriani, Ratri; Salim, Achmad Faishal; Septyan A, Ciptantyo; Rachmad C, Alfin; Mujahidah, Amirah; Wati, Sisca Meida (Indonesian Journal of Dental Medicine, 2024)
Background: Oral cancer is a life-threatening disease that has 377.713 new cases every year and 60% of the 5-year overall survival rate globally. Approximately 84–97% of oral cancer arises from squamous cells, categorized as oral squamous cell carcinoma (OSCC). MiR-21 is a single-stranded, non-coding RNA that has been studied for its role in carcinogenesis. Overexpression of miR-21 is found in various cancers and is linked to a poor prognosis. However, few studies analyze the expression of miR-21 as a diagnostic and prognostic biomarker in oral cancer. Purpose: This review aimed to describe the expression of miR-21 as a novel diagnostic and prognostic biomarker in oral cancer. Review: MiR-21 was found to be upregulated in various cancers, including oral cancer. miR-21 targets several tumor suppressors such as PTEM, TPM1, and PDCD4 to modulate characteristics linked to cancer prognosis, including cell proliferation, apoptosis, invasion, and metastasis. Furthermore, the constant increase of miR-21 expression in healthy oral mucosa to oral potentially malignant disease to OSCC demonstrated its diagnostic value. Conclusion: miRNA-21 may act as a novel diagnostic and prognosticbiomarker of oral cancer.